2006
DOI: 10.1103/physrevb.73.039902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Adsorption and diffusion of Pt and Au on the stoichiometric and reducedTiO2rutile (110) surfaces [Phys. Rev. B72, 081407(R) (2005)]

Abstract: The absolute binding energies of Pt on the stoichiometric and reduced TiO 2 ͑110͒ surfaces should be lower by 0.48 eV compared to the values reported in our paper. This results in a uniform shift of the energy scale in Fig. 2͑a͒ and Fig. 3͑a͒. The new Fig. 2͑a͒ and 3͑a͒ with the updated energy scale are shown below. The correct binding energies of Pt to the stoichiometric and reduced surfaces at the most favorable sites should be 2.03 eV ͑2.14 eV for 3 ϫ 2 cells͒ and 3.80 eV ͑3.55 eV for 4 ϫ 2 cells͒, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
49
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 0 publications
14
49
1
Order By: Relevance
“…The calculated adsorption energies for the periodic slab and PEEC models are listed in Table I. Pt adsorption energies for the hollow site ͑H͒, obtained from the periodic slab models, agree well with the previously reported values by Iddir et al 51,52 These authors predicted, using the PW91 functional, 36 that Pt adsorption on the hollow site ͑H͒ is more stable than Pt adsorption on top of a surface oxygen atom ͑T͒. Although our periodic slab calculations with PBE functional predict the adsorption of Pt at the T site to be more favorable, the adsorption energy difference for the H and T sites is less than 0.1 eV.…”
Section: A Adsorption Of Pt On the Stoichiometric Tio 2 "110… Surfacesupporting
confidence: 87%
See 1 more Smart Citation
“…The calculated adsorption energies for the periodic slab and PEEC models are listed in Table I. Pt adsorption energies for the hollow site ͑H͒, obtained from the periodic slab models, agree well with the previously reported values by Iddir et al 51,52 These authors predicted, using the PW91 functional, 36 that Pt adsorption on the hollow site ͑H͒ is more stable than Pt adsorption on top of a surface oxygen atom ͑T͒. Although our periodic slab calculations with PBE functional predict the adsorption of Pt at the T site to be more favorable, the adsorption energy difference for the H and T sites is less than 0.1 eV.…”
Section: A Adsorption Of Pt On the Stoichiometric Tio 2 "110… Surfacesupporting
confidence: 87%
“…In contrast, studies on the Pt/ TiO 2 ͑110͒ system are scarce. Iddir et al 51 studied the adsorption and diffusion of a single Pt atom on stoichiometric and reduced TiO 2 ͑110͒ surfaces and later discussed the interaction of Pt 2 with the reduced TiO 2 ͑110͒ surface. 52 A few other reports were also made on the interaction of small Pt clusters with the anatase TiO 2 ͑101͒ surface.…”
Section: Adsorption Of Au N and Pt N "N=23… Clusters On The Stoimentioning
confidence: 99%
“…Previous theoretical works found that spin polarization is negligible in the Pt/TiO 2 (110) system 075401-2 [10,11], and we have confirmed it in our preliminary tests. To study the adsorption of single Pt atoms on TiO 2 (110)-(1 × 1), we started by building a 2 × 1 (5.9Å × 6.6Å) supercell and sampling the Brillouin zone with a 2 × 2 Monkhorst-Pack k-point mesh.…”
Section: B Computational Detailssupporting
confidence: 89%
“…The subangstrom spatial resolution achieved in this work, together with density functional theory (DFT) calculations, has revealed the interaction of Pt atoms with a class of surface defects, vacancies of basal threefold coordinated oxygen atoms that are located in the same plane as the Ti atoms, that have not been identified in previous STM studies [9]. This study concludes that the most favorable Pt adsorption site is not on the oxygen vacancy on the top bridging oxygen rows predicted by previous DFT studies [10][11][12], but on these new vacancy sites.…”
Section: Introductionsupporting
confidence: 56%
“…This is because of the strong interaction between the Au atom and oxygen defect site which is due to the charge transfer, ionic interaction, and coordination bond between them [22][23][24][46][47][48][49][50][51]. Owing to the difference between interactions with the defect sites (Cl in Cl-adsorbed TiO 2 and oxygen defect in reduced TiO 2 ), the barriers of Au atom diffusions on x00-x04, x12-x16 for reduced TiO 2 [ Fig.…”
Section: A Results Of Au/cl-adsorbed Tio2mentioning
confidence: 99%